The Role of the Management in the Development of the Internal Control System of the Company - Kanapickienė, Rasa (Ekonomika, 2001)
the role of the internal control does nol limit itself to that of a mechanism aimed at identifying violations or of a whole complex of means which ensure the safety of property and the reliability of accounting records. The internal control proves to become a flexible tool of management, which helps the company to achieve its goals. The article deals with the above aspects of the development and assessment of the internal control.The paper analyses the role of the management in the process of the development of the internal control system of the company, and presents a methodology, which enables to identify the management’s influence on the control system.It is suggested that the internal regulations, which arc an important element of the environment, should be included alongside with the internal and external factors of the internal control. The article shows that the internal regulations, which present a system of internal and external standard instruments regulating the activities of the company, is a flexible and variable link both to individual factors of the internal control and the legal documents which govern the company’s activities OD the state level The paper presents a packet of internal regulations documentation which can be applied in practise.The analysis of the development of an effective internal control system emphasises the crucial role of the management. Consequently, the control environment factors are arranged from the management-related point: the factors, which influence the management; the effect of the management’s standpoint on the internal control; the control mechanism, implemented by the management.The article also presents the analysis of the factors of the internal control environment, which reflect the control mechanism implemented by the management, frames the major requirements for an effective control system, and suggests questionnaires which can help to appraise how the requirements are met in the company. The methodology can be used by auditors and heads of companies in their practical work to assess the standing of the existing control in the company.The article also covers the methods of assembling companyrelated information and substantiates the advantages of questionnaires.